2019
DOI: 10.1097/cm9.0000000000000325
|View full text |Cite
|
Sign up to set email alerts
|

Cryoglobulinemic vasculitis and glomerulonephritis

Abstract: Objective:Cryoglobulinemia often causes systemic vasculitis, thereby damaging to skin and internal organs including kidneys, even life-threatening. This review aimed to introduce the advances in understanding, detection, and treatment of this disease in recent years, with a particular concern to clinical practice.Data sources:All the data in this review were from the English or Chinese literature in the PubMed and China National Knowledge Infrastructure databases as of March 2019.Study selection:This review se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 74 publications
(177 reference statements)
1
13
0
6
Order By: Relevance
“…Cryoglobulinemia was classified by the Brouet criterion into 3 types, typeI, II, and III subtype. Their incidence respectively accounts for approximately 10–15%, 60–70% and 20–30% of cryoglobulinemic syndrome [ 39 ]. Kidney is frequently affected in mixed (Type II and III) cryoglobulinemia, and to a lesser degree in typeIcryoglobulinemia [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryoglobulinemia was classified by the Brouet criterion into 3 types, typeI, II, and III subtype. Their incidence respectively accounts for approximately 10–15%, 60–70% and 20–30% of cryoglobulinemic syndrome [ 39 ]. Kidney is frequently affected in mixed (Type II and III) cryoglobulinemia, and to a lesser degree in typeIcryoglobulinemia [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that the rapid deterioration of her glomerular filtration function was the result of capillary clog as well as a strong inflammatory reaction in the glomeruli. Although membranoproliferative glomerulonephritis (MPGN) is the predominant pathological phenotype accounting for 70 to 90% of all CN cases [ 39 ], other pathological types including endocapillary proliferative GN, mesangial proliferative GN, minimal change disease, and focal segmental glomerular sclerosis have been reported also [ 9 , 19 , 42 ], and they might correspond to a lower grade of inflammation and proliferation [ 43 ]. Interestingly, cellular phenotypic analysis has revealed that the endocapillary hypercellularity and capillary wall duplication in CN are sometimes the results of monocytic infiltration, rather than actual endothelial proliferation and mesangial cell and matrix interposition [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such patients can also exhibit cardiac ischemia, neuropathy, and gastrointestinal bleeding. Over 30% of patients also develop membranoproliferative glomerulonephritis and in some cases pulmonary vasculitis, which results in a worse prognosis [2].…”
Section: Resultsmentioning
confidence: 99%
“…Mixed cryoglobulinemia is associated with HCV in 70% to 90% of cases [2]. Less than 100 cases of mixed cryoglobulinemic vasculitis following SVR after HCV infection have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation